Pengaruh Promosi, Brand Image Terhadap Minat Beli Konsumen Pada Produk Ms Glow Men ( Studi Kasus Mahasiswa Manajemen Unisma 2019 ) - Syamsuddin, Moch; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The aim of this are research is to analyze the influence of promotions and brand image on consumer buying interest in Ms Glow Men products (Case Study of Unisma Management Students class of 2019). The sample in this research was management students from the Faculty of Economics and Business, Unisma Malang, class of 2019, totaling 86 people, taken from a population of 598 people using the Slovin formula. The results of this research show that 1) Promotion variables, brand image have a significant effect on intention to purchase Ms Glow Men products, 2) Promotion variables have a significant and positive effect on intention to purchase Ms Glow Men products, 3) Promotion variables have a significant and positive effect on intention to purchase products Ms Glow Men, 4) The Brand Image variable has a significant and positive effect on the intention to purchase Ms Glow Men products. Keywords: Promotion, Brand Image, Purchase Intention